PENGARUH EDUKASI GIZI ONLINE TERHADAP PENGETAHUAN GIZI DAN ASUPAN VITAMIN C SERTA ZAT BESI SISWA SMP - Putri Aulia Arza; Helmizar Helmizar; Dhiya Fahdila Rahmah (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Nutrition education for children is important to instill healthy eating habits from an early age. The aim of the study was to analyze the effect of nutrition education on nutritional knowledge and intake of vitamin C and iron for students of SMPN 1 Bayang. This type of research is a quasi experimental design with a pre-post control group design approach. The research was conducted in February - September 2020 at SMPN 2 Bayang. Nutritional education using a zoom application and accompanied by social media (whatsapp group) carried out every 2 weeks for 6 weeks as much as 3 times nutrition education. Data collection was carried out by phone and google form. Data analysis using paired sample t-test analyzed the mean differences in the level of knowledge, and intake of micronutrients (vitamin c and iron). Results Based on the social media-based nutrition education, it was found that nutritional knowledge and vitamin C intake increased significantly (P <0.05). Conclusion Social media-based nutrition education can increase student knowledge and student vitamin C intake. Recommendation It is better if nutrition education is done intensively so that it can change students' behavior.Â Keywords : online nutrition education; nutritional knowledge; adolescents; Vitamin C intake; Iron intakeÂ